Citation Analysis for Five Serbian Authors in Web of Science, Scopus and Google Scholar - Filipi Matutinović, Stela (Infotheca - Journal for Digital Humanities; Vol 8 No 1/2 (2007): Infotheca - Journal of Informatics and Librarianship, 2024)
Citation analysis for five Serbian authors from different scientific fields was performed for the period 1998-2006 according to their full bibliographies in two commercial databases (Web of Science and Scopus) and one freely available on the Internet (Google Scholar). The results show big differences between numbers of citations gathered in those databases, suggesting that citation analysis in the Web of Science should not be used as a main indicator for scientific performance for Serbian authors, at least not in all scientific disciplines. The most relevant results from Web of Science, the resource used officially for citation analysis in Serbia, were acquired for an author working in oncology, and the least relevant for computer sciences.